Game-theoretic foundations of monetary equilibrium - Gabriele Camera; Alessandro Gioffré (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
Monetary theorists have advanced an intriguing notion: we exchange money to make up for a lack of enforcement, when it is difficult to monitor and sanction opportunistic behaviors. We demonstrate that, in fact, monetary equilibrium cannot generally be sustained when monitoring and punishment limitations preclude enforcement - external or not. Simply put, monetary systems cannot operate independently of institutions - formal or informal - designed to monitor behaviors and sanction undesirable ones. This fundamental result is derived by integrating monetary theory with the theory of repeated games, studying monetary equilibrium as the outcome of a matching game with private monitoring.
urn:nbn:de:hebis:30:3-317888
Keywords: E4; E5; C7; 330; Social norms; repeated games; cooperation; payment systems